Poland in her heart (on the occasion of the 90th birthday of Professor dr. Martina Orožen) - Tokarz, Emil (Slavia Centralis, 2021)
The paper is written in honor of full professor Martina Orožen, an expert in historical grammar and dialectology of the Slovene language, who is celebrating her 90th birthday. She is presented as the highest authority in the profession; she created a language school to research the diachrony of the Slovene language with her students – her successful scientific research path began in 1962, when she came to Warsaw and Krakow for a short professional training.